THE EFFECTIVENESS OF UNIVERSAL HEALTH PROGRAM SOCIALIZATION BY BPJS KESEHATAN TO THE COMMUNITY OF MATARAM CITY - Windy, Tria Widyantari; Muchammadun; Andri Kurniawan (Universitas Islam Negeri Mataram, 2022)
Factors that cause the lack of interest of the public to use BPJS services are assumptions that it is useless to use BPJS if it is not used, let alone having to register a family. The case is that the underprivileged community becomes twice-minded and burdensome to them. This research uses qualitative research. The data collection method used is an interview, observation, and documentation, while the analysis method used is interactive model analysis. The results showed that the socialization of BPJS Kesehatan is very important for the community. However, BPJS Kesehatan in Mataram city its programs in several sub-districts and the lack of socialization makes people not know about the importance of BPJS Kesehatan. The conclusion of the study shows that BPJS Kesehatan has not been optimal in conducting socialization which makes some people say that BPJS socialization is not effective.